Effect of Psychiatric Morbidity on Quality of Life among Gynaecologic Cancer Survivors - Ranjini Nanjaiah; V Roopadevi (Medsci Publications, 2017)
Introduction:All these years with the invention of newer modalities of treatment and investigations, cancer patients' survival is improved but notthe life after it. Recently focus has shifted from curative aspect to preventive aspect and promoting healthy life. To achieve this an attempt is made to identify the factors affecting the quality of life of gynaecologic cancer survivors. Methods: This is a cross sectional study involving 131 gynaecological cancerpatients who were evaluated using HADS and WHOQOL-BREF Questionnaire. The scores were analysed for any significant association using one-way ANOVA. Results: Depression had negative correlation with psychological domain with p value 0.009 which is highly significant. There is a significant difference in physical domain scores between cases and borderline subjects of anxiety with p value 0.006.Women with psychiatric morbidity had physical and psychological domain affected significantly with p value 0.003 and 0.048 respectively. Conclusions: Now, it is the time to focus on improving the quality of life of these cancer survived patients by early recognition and treatment of psychiatric illness and training them in positive coping abilities. Psychosocial care, with its goals of relieving emotional distress and promoting well-being, is central to efforts to improve the quality of patients' lives.